Relation of human development and sport trajectory in Futsal practitioners: a scope review (Research, Society and Development, 2022)
Objective: To map and categorize studies found in the literature with the themes of human development and sports trajectory related to Futsal practitioners. Method: Scoping Review, a method that allows identifying the evidence available in a given field and verifying the main characteristics and/or factors related to a concept. This method was performed through searches in the databases of WEB of SCIENCE, SCOPUS, BVS, ERIC, SportDiscus/EBSCO, REDALYC and CAPES Periodical, from 2011. Considering the descriptors "human development", "sports", " team sports” and its correspondents in Portuguese and Spanish, in addition to the keywords: Futsal and sports trajectory, using the Boolean operators 'AND' and 'OR' Results: The search resulted in 1456 articles, with 5 articles that presented a relationship of Futsal with the variables of human development and sports trajectory. The articles presented the study variables in isolation, that is, human development x Futsal and sports trajectory x Futsal, with no relationship between them. In both areas, benefits were presented to practitioners through sport. Conclusion: different instruments were identified to measure each theme; it found the lack of studies that relate the two selected variables. This review can strengthen the importance of a sporting environment in the development of practitioners and the need for further studies in these areas.